2016
DOI: 10.1111/jfpe.12403
|View full text |Cite
|
Sign up to set email alerts
|

Alternative Thawing Methods for the Blanched/Non‐Blanched Potato Cubes: Microwave, Ohmic, and Carbon Fiber Plate Assisted Cabin Thawing

Abstract: The effects of conventional-C, carbon fiber plate assisted cabinet heater-CPAC, ohmic-OT, and microwave thawing-MT techniques on changes of some quality characteristics and resistant starch (RS) content of potato (Solanum tuberosum L.) cubes (18 3 18 3 18 mm) were investigated. The effects of blanching prior to the freezing on thawing characteristics were also determined. The thawing times of non-blanched samples were determined as 23,580 6 485 s, 5360 6 40 s, 205 6 18.25 s and 19.26 6 1.49 s for conventional,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 25 publications
3
23
0
3
Order By: Relevance
“…KFKK ünitesinin alt ve üst kısmının iç yüzeyleri karbon fiber ısıtıcı plakaları ile kaplanmıştır ve ünite iç ortam sıcaklığı ayarlanabilmektedir [20] [44]. Bu yaklaşımlardan biri olan film teorisi, kurutma işlemi gibi karmaşık aktarım mekanizmalarının pratik çözümü amacıyla havanın difüze olmayan bileşen olduğu ve durağan ortam olarak kabul edildiği durumda, su buharının hava içinde aktarımını moleküler difüzyon tetikli-taşınımla kütle aktarımı olarak kabul etmektedir.…”
Section: Karbon Fiber Destekli Kabin Kurutucuda Kurutma İşlemiunclassified
“…KFKK ünitesinin alt ve üst kısmının iç yüzeyleri karbon fiber ısıtıcı plakaları ile kaplanmıştır ve ünite iç ortam sıcaklığı ayarlanabilmektedir [20] [44]. Bu yaklaşımlardan biri olan film teorisi, kurutma işlemi gibi karmaşık aktarım mekanizmalarının pratik çözümü amacıyla havanın difüze olmayan bileşen olduğu ve durağan ortam olarak kabul edildiği durumda, su buharının hava içinde aktarımını moleküler difüzyon tetikli-taşınımla kütle aktarımı olarak kabul etmektedir.…”
Section: Karbon Fiber Destekli Kabin Kurutucuda Kurutma İşlemiunclassified
“…Ohmic heating can be used for different purposes in processing of food materials such as heating, pasteurization, cooking, sterilization, blanching, thawing, etc. (Bozkurt & Icier, 2010a, 2010b, 2010c; Içier et al, ; Icier, Yucel Sengun, Yildiz Turp, & Arserim, ; Icier, Cokgezme, & Sabanci, ; Icier, Yildiz, Sabanci, Cevik, & Cokgezme, ; Ozkan, Ho, & Farid, ; Palaniappan & Sastry, 1991a, 1991b; Roberts, Balaban, & Luzuriaga, ; Sensoy & Sastry, ; Wang & Sastry, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, in traditional heating methods, the heat is transmitted from the surface to the inside of the food. The popularity of microwave heating increases in heat treatment applications because of increasing preference for high quality products that can be prepared in a short period of time along with the development of technology [11,12,[16][17][18][19][20] However, the effect of microwave frying on acrylamide content of potato strips has also been studied recently and it was found that the acrylamide content of microwave fried potatoes was lower compared to those fried in conventional deep fryer because of the shorter frying time [11]. There are few studies in literature about the effects of microwave frying on acrylamide formation.…”
Section: Introductionmentioning
confidence: 99%